Geochemistry of Water and Gas Emissions From Cuicocha and Quilotoa Volcanic Lakes, Ecuador - Melián, G. V.; Toulkeridis, T.; Pérez, N. M.; Hernández, P. A.; Somoza, L.; Padrón, E.; Amonte, C.; Alonso, M.; Asensio-Ramos, M.; Cordero, M. (Frontiers in Earth Science, 2021)
There are hundreds of volcanic lakes around the world that represent an important hazard due to the potential occurrence of phreatomagmatic or limnic eruptions. Variations in geochemical and geophysical parameters could help to identify potential risks for these events. Cuicocha and Quilota volcanic lakes, located at the North Andean Volcanic Zone of Ecuador, are geologically young, with gas emissions manifested mainly as CO2 via bubbling gases. Both lakes present a limited monitoring record. Therefore, volcanic monitoring is a priority task due to the potential hazard they represent by the possibility of water stratification and CO2 accumulation. During 2012-2018 period, geochemical investigation based mainly on diffuse CO2 surveys and analyzing the chemical and isotopic composition of bubbling gases has been carried out at Cuicocha and Quilotoa lakes. Additionally, vertical profiles of water columns were conducted in both lakes to investigate the possibility of water stratification and CO2 accumulation in the lakes. A bathymetric study was also carried out in Quilotoa in 2017, giving further information about the degasification processes and the morphology of the lake bottom. The computed diffuse CO2 output for Cuicocha volcanic lake (3.95 km2) showed a range from 53 to 652 t d−1 for the period 2006–2018, with a maximum value in 2012, coinciding with a maximum of the 3He/4He ratio measured at the bubbling gases and an increase in the seismic activity with an episode of long-period seismicity recorded in 2011–2012. For Quilotoa volcanic lake (3.50 km2) diffuse CO2 output was estimated between 141 and 536 t d−1 for the period 2014–2018. The chemical and isotopic data show that Cuicocha has a chemical composition typical of worldwide superficial shallow waters and aquifers, while Quilotoa shows a chemical composition typical of crater lakes in active volcanic systems. The distribution of the dissolved gas composition along the vertical profiles shows the existence of different water masses in both lakes, with an increase in the concentration of dissolved gases with depth. The carbon isotopic signature indicates an endogenous origin of the CO2, with a greater contribution in the stratification zone in both lakes. This study shows methods applicable to other volcanic lakes of the world to monitor their activity and potential risks.